PENGARUH MEDIA PERMAINAN MONOPOLI TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD SWASTA GKPS NO 1 PEMATANGSIANTAR - Sidabalok, Nova E; Sijabat, Jernita M; Munthe, Irawati; Pakpahan, Nissi N (Komunitas Manajemen Kompetitif, 2024)
This research aims to determine whether there is an influence of the Monopoly game media on the science learning outcomes of fourth-grade students at GKPS No. 1 Private Elementary School in Pematangsiantar. Sampling was conducted using the purposive sampling technique. The sample in this study consists of 16 students.From the results of the validity test, 20 questions were found to be valid and 5 questions were found to be invalid. In the reliability test, the Cronbach Alpha value was > 0.70, specifically 0.889 > 0.70, indicating that the questions are reliable. Based on the difficulty level test, it can be concluded that the questions are classified as medium difficulty. The method used in this research is the quantitative method, and the design used in this research is the Pre-experimental Design. The chosen design form is the One Group Pretest-Posttest. The subjects in this research are 16 students from the fourth grade of SD Swasta GKPS No 1 Pematangsiantar. The data from this research shows that the influence of the Monopoly game media on science learning outcomes has a pretest average score of 57.5, while the posttest average score is 82.1, indicating an impact on the science learning outcomes of fourth-grade students. The final results of this study are considered successful because in the t-test, t using the Microsoft Word 2010 tool then calculated = 4,046 and t_table = 1,761, with t_calculated > t_table = 4,046 > 1,761, thus Ho is rejected and Ha is accepted. With this explanation, it can be concluded that there is an influence of the Monopoly game media on the science learning outcomes of the 4th-grade students at GKPS No. 1 Private Elementary School in Pematangsiantar. Keywords: